A Ricardian rationale for the WTO rules on R&D subsidies - KOH, Yumi (Institutional Knowledge at Singapore Management University, 2020)
The WTO subsidy rules use two key criteria, specificity and adverse effects, to regulate R&D subsidies. Using the model of Dornbusch et al. (1977), we offer a Ricardian rationale for the regulatory criteria.